Economic impact of genomic diagnostics for intermediate‐risk acute myeloid leukaemia - Cressman, S; Karsan, A; Hogge, DE; McPherson, E; Bolbocean, C; Regier, DA; Peacock, SJ (Wiley, 2016)
Acute Myeloid Leukaemia (AML) is a rare but serious group of diseases that require critical decision-making for curative treatment. Over the past decade, scientific discovery has revealed dozens of prognostic gene mutations for AML while sequencing costs have plummeted. In this study, we compared the cost-effectiveness of multigene integrative analysis (genomic analysis) with the standard molecular testing currently used for diagnosis of intermediate-risk AML. We used a decision analytic model with data for costs and outcomes from British Columbia, Canada, to assess the long-term (10-year) economic impacts. Our results suggest that genomic analysis would result in a 26% increase in the use of first-remission allogeneic stem cell transplantation. The resulting treatment decisions and downstream effects would come at an additional cost of CAD12 556 [2013 Canadian dollars (CAD)] per person and the incremental cost-effectiveness ratio would be CAD49 493 per quality-adjusted life-year gained. Cost-effectiveness was dependent on quality of life during the long-term (5–10) years of survival, relapse rates following first-remission chemotherapy and the upfront cost of transplantation. Non-relapse mortality rates, short-term quality of life and the cost of genomic sequencing had only minor impacts. Further research on post-remission outcomes can lead to improvements in the cost-effectiveness of curative treatments for AML.